Photoemission spectrum in paramagnetic FeO under pressure: Towards an ab initio description - S. Di Sabatino; J. Koskelo; J. A. Berger; P. Romaniello (Physical Review Research, 2021)
In this paper we provide an exhaustive study of the photoemission spectrum of paramagnetic FeO under pressure using a refined version of our recently derived many-body effective energy theory (MEET). We show that, within a nonmagnetic description of the paramagnetic phase, the MEET gives an overall good description of the photoemission spectrum at ambient pressure as well as the changes it undergoes by increasing pressure. In particular at ambient pressure the band gap opens between the mixed Fe t_{2g} and O 2p states and the Fe 4s states and, moreover, a d-d gap opens, which is compatible with a high-spin configuration (hence nonzero local magnetic moments as observed in experiment), whereas with decreasing pressure the band gap tends to close, t_{2g} states tend to become fully occupied, and e_{g} states tend to become fully unoccupied, which is compatible with a low-spin configuration (hence a collapse of the magnetic moments as observed in experiment). This is a remarkable result, since, within a nonmagnetic description of the paramagnetic phase, the MEET is capable to correctly describe the photoemission spectrum and the spin configuration at ambient as well as high pressure. For comparison we report the band-gap values obtained using density-functional theory with a hybrid functional containing screened exchange (HSE06) and a variant of the GW method (self-consistent COHSEX), which are reliable for the description of the antiferromagnetic phase. Both methods open a gap at ambient pressure, although, by construction, they give a low-spin configuration; increasing pressure they correctly describe the band-gap closing. We also report the photoemission spectrum of the metallic phase obtained with one-shot fully dynamical GW on top of the local-density approximation, which gives a spectrum very similar to dynamical mean-field theory results from literature.